An assessment of flood mitigation measures in Accra, Ghana - Attipoe, Selasi Kofi (2015)
A thesis submitted to the Department of Planning, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of degree of Master of Science in Development Planning and Management